2021
DOI: 10.3389/fphar.2021.647481
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine Protects Against Diabetic Cardiomyopathy by Regulating Vagal Activity, Gut Microbiota, and Branched-Chain Amino Acid Catabolism in Diabetic Mice

Abstract: The disruption of gut microbes is associated with diabetic cardiomyopathy, but the mechanism by which gut microbes affect cardiac damage remains unclear. We explored gut microbes and branched-chain amino acid (BCAA) metabolite catabolism in diabetic cardiomyopathy mice and investigated the cardioprotective effect of pyridostigmine. The experiments were conducted using a model of diabetic cardiomyopathy induced by a high-fat diet + streptozotocin in C57BL/6 mice. The results of high-throughput sequencing showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
(88 reference statements)
2
17
0
Order By: Relevance
“…Also, pyridostigmine was found to promote BCAAs catabolism by enhancing vagal activity and attenuating intestinal barrier injury and gut bacteria dysbiosis in diabetic cardiomyopathy mice. Pyridostigmine was also found to enhance cardiac BCAAs catabolism by upregulating BCAT2 and PP2Cm and downregulating p-BCKDHA/BCKDHA and BCKDK ( 78 ).…”
Section: Role Of Branched-chain Amino Acids and Branched-chain α-Keto...mentioning
confidence: 99%
“…Also, pyridostigmine was found to promote BCAAs catabolism by enhancing vagal activity and attenuating intestinal barrier injury and gut bacteria dysbiosis in diabetic cardiomyopathy mice. Pyridostigmine was also found to enhance cardiac BCAAs catabolism by upregulating BCAT2 and PP2Cm and downregulating p-BCKDHA/BCKDHA and BCKDK ( 78 ).…”
Section: Role Of Branched-chain Amino Acids and Branched-chain α-Keto...mentioning
confidence: 99%
“…Bckdha has been reported to play a protective role in liver fibrosis ( Wang et al, 2012 ). Conversely, Yang et al suggested that pyridostigmine downregulated p- Bckdha / Bckdha to improve cardiac branched-chain amino acid catabolism and alleviated cardiac hypertrophy and fibrosis in diabetic cardiomyopathy mice ( Yang et al, 2021 ). The expression of Lpl contributed to hepatic fibrosis in nonalcoholic steatohepatitis ( Teratani et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, our results showed that SalA could increase ZO-1, Occludin, and Claudin-1 expressions and decrease LPS, IL-6, and TNF-α levels. Accordingly, the preceding report has noted that DM diminishes tight junction proteins, including ZO-1, occludin, and claudin-1, and increases intestinal permeability to damage the intestinal barrier [ 60 ]. Additionally, the decline in intestinal permeability is positively-associated with LPS levels and DM patients exhibit elevated plasma LPS [ 17 , 46 ].…”
Section: Discussionmentioning
confidence: 99%